(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
Between 1980 and 1981, Aimone Sambuy realized a few works inspired by his memories of a trip to Egypt. It was the occasion to conduct personal reflections on the themes of memory and to reinvent substantially the technique of watercolour.